A qualitative analysis of parents’ experiences while their neonates with congenital heart disease require intensive care - Catapano, Francesca; Steinwurtzel, Rochelle; Parravicini, Elvira; Wool, Charlotte (Frontiers in Pediatrics, 2024)
Objective. To better understand the experience of parents with neonates with congenital heart diseases (CHD) admitted to a neonatal intensive care unit (NICU) in order to identify challenges faced by parents and discover support strategies helpful in positive coping. Study design. Prospective cohort study of parents of neonates with CHD. Parents completed a questionnaire with open ended questions regarding their experience and feeling during the hospitalization within one week of the child discharge from the NICU. Krippendorff's content analysis was used to examine data. Results. Sixty-four parents participated. Three themes were highlighted -Dialectical parental experiences, Suboptimal Parental Experiences and Positive Parental Experiences -describing the state of being and feelings that these parents face. Through this analysis, we were able to develop clinical considerations and identify coping strategies.The understanding of parental experience and challenges when dealing with their child admitted in the NICU is crucial to identify coping strategies to promote adaptation and enhance the development of positive coping mechanisms.